Iron accumulation causes impaired myogenesis correlated with MAPK signaling pathway inhibition by oxidative stress. Issue 8 (30th May 2019) - Ikeda, Yasumasa; Satoh, Akiho; Horinouchi, Yuya; Hamano, Hirofumi; Watanabe, Hiroaki; Imao, Mizuki; Imanishi, Masaki; Zamami, Yoshito; Takechi, Kenshi; Izawa‐Ishizawa, Yuki; Miyamoto, Licht; Hirayama, Tasuku; et al.
ABSTRACT: Skeletal muscle atrophy is caused by disruption in the homeostatic balance of muscle degeneration and regeneration under various pathophysiological conditions. We have previously reported that iron accumulation induces skeletal muscle atrophy via a ubiquitin ligase–dependent pathway. However, the potential effect of iron accumulation on muscle regeneration remains unclear. To examine the effect of iron accumulation on myogenesis, we used a mouse model with cardiotoxin (CTX)‐induced muscle regeneration in vivo and C2C12 mouse myoblast cells in vitro . In mice with iron overload, the skeletal muscles exhibited increased oxidative stress and decreased expression of satellite cell markers. Following CTX‐induced muscle injury, these mice also displayed delayed muscle regeneration with a decrease in the size of regenerating myofibers, reduced expression of myoblast differentiation markers, and decreased phosphorylation of MAPK signaling pathways. In vitro, iron overload also suppressed the differentiation of C2C12 myoblast cells but the suppression could be reversed by superoxide scavenging using tempol. Excess iron inhibits myogenesis via oxidative stress, leading to an imbalance in skeletal muscle homeostasis. —Ikeda, Y., Satoh, A., Horinouchi, Y., Hamano, H., Watanabe, H., Imao, M., Imanishi, M., Zamami, Y., Takechi, K., Izawa‐Ishizawa, Y., Miyamoto, L., Hirayama, T., Nagasawa, H., Ishizawa, K., Aihara, K.‐I., Tsuchiya, K., Tamaki, T. Iron accumulation causes impaired myogenesis correlated with MAPK signaling pathway inhibition by oxidative stress. FASEB J. 33, 9551–9564 (2019). www.fasebj.org